Implementasi Kaidah Al-Yaqinu La Yuzalu Bi Al-Syakki Dalam Ibadah - Fitri Amanda Hsb; Tasya Afrianti; M. Yusuf Alamsyah; Dicky Alamsyah Pardede; Rayhan Riend al-Afiq; Rahmad Hidayat (Tabayyun : Journal Of Islamic Studies, 2025)
The rule (qaidah) of Al-Yaqinu La Yuzalu bi Al-Syakki is present as a fundamental principle that provides guidance in dealing with these doubts. This rule was first formulated by classical scholars and continues to develop into one of the important pillars in decision-making of Islamic law. This study examines the implementation of the fiqh rules "Al-Yaqinu La Yuzalu bi Al-Syakki" (belief cannot be eliminated by doubt) in the context of the implementation of Muslim worship. This rule is one of the fundamental principles in Islamic law that has broad implications in various aspects of worship. This study aims to analyze the application of these rules in various contemporary worship problems and their relevance to modern life. This research is a doctrinal research with a literature study approach. That is a study by reading from various references with the object of research, namely about how to implement the rules in the matter of worship and muamalah. The results of the study found that this rule is one of the foundations of the postulates used in the issue of worship and muamalah.